Caracterização mineral dos rejeitos de bauxita da Mina de Juruti - Pa. - SANTOS, Brenda Carvalho dos (Instituto de Engenharia e Geociências, 2024)
Bauxite is the main source of alumina having different types of betonies deposits, characterizing its specific uses, according to its mineralogical composition and associated impurities. At the Juruti - Pará mine, the method of mining and dismantling of the barren ore that is mechanically made with tractors is adopted. The treatment of the ore involves only crushing and washing, and no chemical process is used. About 25% of the product extracted from the Juruti mine is discarded for low aluminum content, being denominated tailings and not going through any specific analysis and / or monitoring, besides those realized in the own structure of the basin, before being sent where it is deposited. Although there is no chemical process involved in the beneficiation of bauxite, this does not guarantee that the waste generated will not pose a hazard and could represent a serious environmental problem in the future. In the work was carried out to the analysis of the mineralogical composition in order to verify the possibility of sintese new materials. Six samples were collected and submitted to X-ray diffraction (DRX) and X-ray fluorescence (FRX). Preliminarily it was verified with DRX a pattern with the main crystallographic phases: Hematite ( ), Kaolinite ( ), Gibbsite ( ( ) ), Anatase ( ) and Quartz ( ). The FRX measurements confirmed quantitatively with the main oxides: (62,78%); (15,15%); (14,02%); (7,39%), found in each known bauxite sample, and also showed unexpected chemical elements in the locality and in very high amounts. The results show that the composition of the tailings has the potential to be reused in the synthesis of new materials such as increase in construction materials, for example, in addition to contributing to the sustainability and the preservation of accidents such as the disruption tailings dams.